Peran dan Strategi Pokdarwis dalam Pengembangan Ekowisata Berbasis Masyarakat dan Penguatan Ekonomi Lokal di Kabupaten Solok - Budi Mulia (LPPM Universitas Malikussaleh - Indonesia, 2026)
This study aims to analyze the roles and strategies of Tourism Awareness Groups (Pokdarwis) in developing community-based ecotourism and their contribution to strengthening the local economy in Solok Regency. The research employed a qualitative approach with a multiple case study design across three locations: Pokdarwis Salingka Usak, Dewita Tigo Ranah, and Kampung Batu. Data were collected through participant observation, in-depth interviews, and documentation studies, subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicate that Pokdarwis has implemented strategic roles across the dimensions of product development, service standardization, and community empowerment. However, stakeholder relations exhibit performance disparities, where stable collaborative networks with external parties have not been uniformly established. Local economic strengthening strategies were successfully realized through the downstreaming of local wisdom-based products, such as the Balai Sawah Tangah Traditional Market, wood crafts, and tourism services that create new business opportunities for villagers. In conclusion, the effectiveness of Pokdarwis as an economic catalyst heavily relies on the integration of authentic product innovation and organizational capacity building. The implications of this study emphasize the necessity of digital transformation and the expansion of multi-stakeholder partnerships to ensure the sustainability of the ecotourism ecosystem. Future researchers are encouraged to quantitatively measure the economic multiplier effect of ecotourism on farm household welfare